Answer:
42
Step-by-step explanation:
g(-5)=-5.-5+17
=25+17
=42
<u><em>Answer:</em></u>
D. f⁻¹(x) = 2x + 10
<u><em>Explanation:</em></u>
<u>The given is:</u>
<u>To find the inverse, follow the below procedures:</u>
<u>1- Convert f(x) to y. </u>
<u>This will give:</u>
<u>2- Swap the x and y variables.</u>
<u>This will give:</u>
<u>3- Solve for y.</u>
<u>This will give:</u>
<u>4- Replace the y in the above step with f⁻¹(x).</u>
<u>This will give us:</u>
f⁻¹(x) = 2x + 10
Hope this helps :)
56:7=24:3
3x3=27:3
8x2=64:4
45:9=35:7
4x5=10x2
42:6=63:9
28:4=7x1
2x2=36:9